IMPLIKASI PERATURAN MAHKAMAH AGUNG NOMOR : 02 TAHUN 2012 TENTANG PENYESUAIAN BATASAN TINDAK PIDANA RINGAN DAN JUMLAH DENDA DALAM KUHP - Khoiru Dhuhri, Eko Soponyono, Pujiyono (Diponegoro Law Journal, 2012)
The number of cases of theft to the value of small items that are now on trial in the court quite got the attention of the general public. Society considers that it is not fair that criminal matters are considered minor punishable with a penalty of five (5) years, as the threat of theft offenses set forth in Article 362 of the Criminal Code because it is not worth the value of the stolen goods. Associated with it then on February 27, 2012 the Supreme Court ruled Supreme Court Regulation No. 02 Year 2012 on the adjustment of boundaries and the number of minor criminal penalties in the Criminal Code. This study aims to determine the implications of the Supreme Court Regulation No. 02 Year 2012 on the Limitation Adjustments Lightweight Crime and the Criminal Code and the penalty amount to determine the scope of authority of the Rules of the Supreme Court of the stages of the criminal proceedings. The method of approach in writing this law is normative specifications descriptive study analysis. The data collection methods used are literature studies, and data analysis methods used are qualitative. Based on these results it can be concluded that the Supreme Court Regulation No. 02 Year 2012 on the Limitation Adjustments Lightweight Crime Penalties in the Criminal Code and Number can be imposed only at the stage of trial, because investigators and prosecutors are not under the authority of the Supreme Court, so there is no requirement for investigators and prosecutors to submit to the rules made by the Supreme Court. Therefore, at this stage of the examination in any criminal trial that the value of money or goods less than $ 2,500,000.00 (Two million five hundred thousand dollars), the arrest of the perpetrators is not done because it involves misdemeanor. Detention provisions stipulated in the Supreme Court is based on the detention provisions contained in the Criminal Procedure Code. The conclusions of this study are needed legislation to accommodate the Supreme Court Regulation No. 2 of 2012, which binds to the investigator, prosecutor, or the court, considering the value of the money in the Criminal Code no longer compatible with the current state before the passage of the Criminal Code new.